Mengelola Keuangan Secara Syariah dalam Rangka Menumbuhkan Good Money Habit - Masruroh, Aini (Al-Iqtishad: Journal of Islamic Economics, 2013)
The wealth owned by Muslims basically is a trust from Allah that must be spent or distributed responsibly. Good habit in spending money is reflected on how the person makes a financial decision of his own. The main aspect in conducting the financial plan is the ability to save and invest. A person is qualified as having good money habits if he is able to pay themselves first that other interest. Meaning that each earn he have, he is able to allocated it to charity, the primary consumption, and plans for the future. Whereas the spontaneous type might probably refuses to make a financial planningDOI: 10.15408/aiq.v5i1.2111